The influence of anthropogenic pressure on the synthesis of phenolic substances in the leaves of chestnut Aesculus L. - Свідзінська, Н. Б.; Чепурко, А. В. (Problems of Environmental Biotechnology, 2014)
The accumulation of phenolic substances in the chestnut leaves the influence of anthropogenic load in different districts of Kiev, which are distinguished by the level of pollution, was studied.